ANALISIS SEMIOTIK DALAM PUISI “HATIKU SELEMBAR DAUN” KARYA SAPARDI DJOKO DAMONO - Pirmansyah, Pipin; Anjani, Citra; Firmansyah, Dida (IKIP Siliwangi, 2018)
The purpose of this research is to (1) analyze the poem in semiotics (2) to describe the result of poetry analysis entitled Hatiku Selembar Daun by Sapardi Djoko Damono, (3) to define the outline of the theme of the poem. After going through the process of discussion of poetry and semiotic attention, will know tetang meaning and signs of language contained in the poem My Heart One Leaf so conveyed to the reader